Beyond Membership: The Correlation Between English Club Engagement and Students’ Self-Confidence - Yuniarsih Azizah; La Sunra; Chairil Anwar Korompot (PT. Global Research Collaboration, 2026)
This study examined the correlation between students’ engagement in the English Club and their self-confidence in an Indonesian senior high school EFL context. A quantitative correlational design was employed with 50 active members of Collage English Club at SMAN 22 Makassar during the 2025/2026 academic year. Data were collected using two five-point Likert-scale questionnaires measuring student engagement and self-confidence. The scoring sets comprised 16 engagement items representing behavioral, emotional, and cognitive engagement and 21 self-confidence items representing students’ perceived confidence across speaking, listening, reading, writing, and grammatical knowledge. The scoring sets demonstrated strong internal consistency, with Cronbach’s alpha values of .900 for engagement and .952 for self-confidence. The data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, and Pearson Product-Moment correlation in SPSS. Students’ engagement had a mean score of 3.9738 (SD = .61809), while self-confidence had a mean score of 3.4600 (SD = .72548). The correlation analysis revealed a statistically significant moderate positive correlation between engagement and self-confidence, r(48) = .568, p < .001. The findings indicate that students with higher engagement scores tended to report higher self-confidence scores.